2010
DOI: 10.1007/s11130-010-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Rosemary Extracts, Carnosic Acid and Rosmarinic Acid on the Growth of Various Human Cancer Cell Lines

Abstract: The leaves of Rosmarinus officinalis harvested from three different locations of Turkey were extracted by both methanolic and supercritical CO(2) extraction. Subsequently, six extracts and the active compounds, carnosic acid, and rosmarinic acid were applied to various human cancer cell lines including NCI-H82 (human, small cell lung, carcinoma), DU-145 (human, prostate, carcinoma), Hep-3B (human, black, liver, carcinoma, hepatocellular), K-562 (human chronic myeloid leukemia), MCF-7 (human, breast, adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
217
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(232 citation statements)
references
References 21 publications
14
217
0
1
Order By: Relevance
“…For instance, studies with carnosic acid showed that concentrations of 6.25 lg/mL reduced between 13 and 30 % the viability of different types of tumor cells (Yesil-Celiktas et al 2010). Similar effects have been reported for carnosic acid on viability of five human cancer cell lines (Gigante et al 2003).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For instance, studies with carnosic acid showed that concentrations of 6.25 lg/mL reduced between 13 and 30 % the viability of different types of tumor cells (Yesil-Celiktas et al 2010). Similar effects have been reported for carnosic acid on viability of five human cancer cell lines (Gigante et al 2003).…”
Section: Discussionmentioning
confidence: 54%
“…Similar effects have been reported for carnosic acid on viability of five human cancer cell lines (Gigante et al 2003). To the opposite, concentrations of rosmarinic acid ranging from 6.25 to 50 lg/mL (139 lM) showed proliferative effects rather than cytotoxic activity (Yesil-Celiktas et al 2010). Carnosol exhibited growth inhibition 50 % (GI 50 ) values ranging from 3.6 to 26 lM in five tumor cells (Guerrero et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several researches on the antiproliferative effect of rosemary were developed in recent years, such as Yesil-Celiktas et al (2010) who evaluated the activity of aqueous and alcoholic extracts of R. officinalis leaf, at concentrations from 12.50 to 47.55 mg/mL on human cell lines NCI-H82 (lung carcinoma) DU-145 (prostate carcinoma), Hep-3B (hepatocellular carcinoma), K-562 (chronic myelogenous leukemia) and MCF-7 (breast adenocarcinoma) and verified that rosemary significantly inhibited cell division in all these cells. Similarly, Tai et al However, all studies reported on R. officinalis antiproliferative activity have had the cells of their testsystems treated with some clastogenic drug (and so some damage to the genetic material).…”
Section: Resultsmentioning
confidence: 99%
“…The statistical analysis of the data was carried out by the Chi-square test at 5% significance using the software BioEstat (Ayres, 2007). The antiproliferative role of this plant is attributed to the activity of rosmarinidifenol, rosmariquinone and rosmanol (Yesil-Celiktas et al, 2010). According to Visanji et al (2006), high concentrations of these terpenes disrupt the cell cycle in the G 2 phase of the interphase, by interrupting the cytoplasm replication and the onset of chromosome condensation.…”
Section: Obtaining Meristematic Cells For Cytogenetic Analysismentioning
confidence: 99%
“…The anticarcinogenic activity of rosemary is due to the major bioactive compounds such as 1,8-cineole, camphor, and α-pinene [44]. In a similar study where compounds extracted from R. officinalis were tested on various cancer cell lines, such as NCI-H82 (small lung carcinoma), DU-145 (prostate carcinoma), Hep3D (liver carcinoma), K-562 (chronic myelois carcinoma), MCF-7, (breast adenocarcinoma), PC-3 (prostate adenocarcinoma) and MDA-MB-231 (breast adenocarcinoma) the IC 50 values ranged from 8.82 μg/mL to over 100 μg/mL [45].…”
Section: Cytotoxic Activitymentioning
confidence: 99%